Evaluation of phosphate solubilization from phosphoric rock via Aspergillus niger and Penicillium sp - Argotte, Leandro; Barreiro, Oscar Fernando; Cerquera, Néstor Enrique; Castro, Hans Thielin (Revista de Ciencias Agrícolas, 2020)
Phosphoric rock is the main source of phosphorus used in fertilizers. In most cases, it is applied alone or mixed with other nutrients in water; however, its low solubility means that it is not used efficiently, causing excess phosphorus to be wasted. As a result, it generates economic expenses to the farmer, or causing problems of eutrophication in water sources. In this article, different mixtures of solubilizing fungi with coffee pulp stillage were studied to improve phosphates’ solubility in phosphate rock. Despite that in different studies is clear the fungi’s role in P solubilization, its application on soils is still made without any additional treatment. Phosphoric rock samples were obtained from the municipality of Aipe (Huila) and were treated for 6 weeks with coffee pulp stillage (Coffea arabica) and inoculums of Aspergillus niger and Penicillium sp, pH and temperature controlled. The fungus species were obtained from environmental media on PDA culture, then it was isolated and identified on MEA culture according to standard morphologic identification methods. Aspergillus niger showed greater mycelial growth in the stillage and a higher concentration of phosphates dissolved in the aqueous phase (72 ± 31 M) compared to Penicillium sp. The mixture of the two fungi in the treatments allowed to obtain the highest percentage of phosphates (17.8% of the phosphate soluble in H2SO4 40% v / v).